Transformation of the Urban Rail Sector through PPP - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 2009)
The recent proliferation of Public Private Partnership (PPP) projects in numerous cities has transformed the urban rail sector. The enthusiasm for PPPs can be explained by improved understanding of efficiency gains and risks of bundling and unbundling tasks as well as availability and lower cost of private sector finance. The four main PPP approaches identified are: (i) development of new systems through DBFOs (Design- Build-Finance-Operate); (ii) concessioning of rail and subway services; (iii) sale of stateowned operators through share issue privatisation; and (iv) PPPs for infrastructure maintenance and upgrading. This paper examines examples of successes and failures to better understand the complexities involved in PPP decisions and the trade-offs cities make when deciding between alternative strategies.